2022
DOI: 10.1001/jamanetworkopen.2022.41451
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low-Dose Interleukin 2 for Primary Sjögren Syndrome

Abstract: ImportancePrimary Sjögren syndrome (pSS) is a systemic autoimmune disease associated with dysregulated immune cells, with no efficient therapy. There is a need to study potential therapeutic approaches.ObjectiveTo investigate the efficacy, safety, and immune response of low-dose interleukin 2 (LD-IL-2) in the treatment of pSS.Design, Setting, and ParticipantsA double-blind, placebo-controlled randomized clinical trial was conducted with a 2-group superiority design from June 2015 to August 2017. Sixty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…A striking observation was that Treg cells (C2) underwent the least clonal expansion in both VKHD and BD, suggesting that insufficient expansion of Treg cells might posit in the root of losing immune tolerance in autoimmune uveitis. Our previous clinical trials of low-dose IL-2 therapy in systemic lupus erythematosus and Sjogren's syndrome have demonstrated that it could enhance antigenindependent expansions of Treg cells, [36][37][38] thus providing a strategy to improve the poor clonal expansion of Treg cells in autoimmune uveitis. However, IPA analyses also suggest that IL-2 could be involved in the generation of pro-inflammatory CD4 + Tem and CD8 + Tem cells.…”
Section: Discussionmentioning
confidence: 99%
“…A striking observation was that Treg cells (C2) underwent the least clonal expansion in both VKHD and BD, suggesting that insufficient expansion of Treg cells might posit in the root of losing immune tolerance in autoimmune uveitis. Our previous clinical trials of low-dose IL-2 therapy in systemic lupus erythematosus and Sjogren's syndrome have demonstrated that it could enhance antigenindependent expansions of Treg cells, [36][37][38] thus providing a strategy to improve the poor clonal expansion of Treg cells in autoimmune uveitis. However, IPA analyses also suggest that IL-2 could be involved in the generation of pro-inflammatory CD4 + Tem and CD8 + Tem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IL-2 acts as the double-edged sword, although IL-2 signaling can promote an exhausted phenotype, it is also a feasible pathway to reverse CD8 + T-cell exhaustion. Initially, the earliest therapeutic applications of IL-2 were to improve immune responses in cancer patients [ 128 , 129 ]. In present, combining IL-2 treatment with immune checkpoints inhibitors PD-1 has striking synergistic effects for re-invigorating exhausted CD8 + T cells [ 130 ].…”
Section: Factors Related To the Development Of T Cell Exhaustionmentioning
confidence: 99%
“…Autoreactive effector T-cells originate and reinforce pathogenic B-cell responses. Interleukin 2 (IL-2) is the key stimulator of CD4+ T-cells and controls regulatory T-cells (Tregs) ( 49 ). The function of Treg cells was observed to be disrupted in patients with primary SS ( 50 ).…”
Section: Connective Tissue Disease-associated Lung Diseasesmentioning
confidence: 99%
“…Low-dose IL-2 therapy significantly improved disease activity scores and immunological effects in 60 primary SS patients ( 49 ). However, the potential role of this therapy on ILD in SS is not well-defined.…”
Section: Connective Tissue Disease-associated Lung Diseasesmentioning
confidence: 99%